2007
DOI: 10.1016/j.jasms.2007.04.021
|View full text |Cite
|
Sign up to set email alerts
|

The application of a hypothesis-driven strategy to the sensitive detection and location of acetylated lysine residues

Abstract: The©application©of©a©hypothesis-driven©method©for©the©sensitive©determination©of©lysine acetylation© sites© on© enzymatically© digested© proteins© is© described.© Comparative© sensitivity© tests were© carried© out© using© serial© dilution© of© an© acetylated© bovine© serum© albumin© (AcBSA)© digest to©assess©the©performance©of©a©multiple©reaction©monitoring©(MRM)-© based©approach©as compared© to© a© more© conventional© precursor© scanning© (PS)© method.© Both© methods© were© capable of© selectively© detecting©… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 13 publications
0
22
0
1
Order By: Relevance
“…This technique has been recently utilized to quantify putative peptide and protein biomarkers where a proteotypic peptide is selected as a surrogate for the protein of interest [1][2][3][4][5][6][7]. Aptly suited to the multiplex capabilities of this MRM strategy, multiple signature peptides representing a particular protein can then be examined in one experiment allowing for the development of a highly selective, sensitive and high throughput quantitative methodology [1,8].…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This technique has been recently utilized to quantify putative peptide and protein biomarkers where a proteotypic peptide is selected as a surrogate for the protein of interest [1][2][3][4][5][6][7]. Aptly suited to the multiplex capabilities of this MRM strategy, multiple signature peptides representing a particular protein can then be examined in one experiment allowing for the development of a highly selective, sensitive and high throughput quantitative methodology [1,8].…”
Section: Overviewmentioning
confidence: 99%
“…This however greatly increases the search time and cost. While MRM-MS has not been commonly used to focus on acetylation as a PTM like phosphorylation, Griffiths et al, demonstrated an interesting approach [8]. Since acetylation can be detected by the characteristic reporter ion of 126.1 m/z after CID, corresponding to the immonium ion of the acetyl-lysine, the authors utilized a MRM-MS approach to detect acetylation in a test case proteins.…”
Section: Utility Of Mrm Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Detection was achieved within the low fmol (on-column) range and the utility of the application was confirmed by analysing naturally acetylated peptides derived from cytokeratin 8 isolated from a cell lysate by 2D-gel electrophoresis. Using a total of 84 MRM transitions for potential acetylation sites, the authors were able to identify five novel acetylated peptides [113], confirming that the method has the selectivity and sensitivity to identify naturally modified proteins present within a biological matrix.…”
Section: Acetylationmentioning
confidence: 69%
“…Griffiths and co-workers applied a MIDAS-based approach similar to the one developed by the same group for phosphorylation analysis [51,113] to determine the sensitivity of detection of acetylated peptides derived from bovine serum albumin. Once again they found that the MRM method offered >10-fold enhanced sensitivity compared with precursor ion scanning for the immonium ion of acetyl lysine minus NH 3 (mass 126.1 Da).…”
Section: Acetylationmentioning
confidence: 99%